KUPFFER HÜCRESİ - AKTAN, Tahsin Murad; CANBİLEN, Aydan and KEKLİKOĞLU, Nurullah (Cerrahpaşa Medical Journal, 2014)
Background.- Kupffer cells were firstly described by von Kupffer at 1876. In our work we reviewed the function and properties of these cells especially other than fagocytosis whom are cell-cell communication and some clinical importances of these features. Histologic and cell origin properties were also mentioned. Also the effect of donor liver Kupffer cells is stressed for organ transplantation.